2021
DOI: 10.3390/jof7030168
|View full text |Cite
|
Sign up to set email alerts
|

Central Nervous System Mold Infections in Children with Hematological Malignancies: Advances in Diagnosis and Treatment

Abstract: The incidence of invasive mold disease (IMD) has significantly increased over the last decades, and IMD of the central nervous system (CNS) is a particularly severe form of this infection. Solid data on the incidence of CNS IMD in the pediatric setting are lacking, in which Aspergillus spp. is the most prevalent pathogen, followed by mucorales. CNS IMD is difficult to diagnose, and although imaging tools such as magnetic resonance imaging have considerably improved, these techniques are still unspecific. As mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(24 citation statements)
references
References 83 publications
(125 reference statements)
0
21
0
3
Order By: Relevance
“…Cross-reactivity with other pathogenic moulds and yeasts is undesirable, especially in the setting of co-infections comprising R. arrhizus and Aspergillus , Exophiala , and Fusarium species [ 85 , 86 , 87 , 88 , 89 ], where discrimination of the infecting species is needed to optimise treatment with antifungal drugs, and to prevent breakthrough R. arrhizus infections [ 70 , 90 ]. The detection of mucormycosis is not possible using the pan-fungal (1→3)-β- d -glucan (BDG) test, since the Mucorales lack this carbohydrate in their cell walls [ 91 ].…”
Section: Discussionmentioning
confidence: 99%
“…Cross-reactivity with other pathogenic moulds and yeasts is undesirable, especially in the setting of co-infections comprising R. arrhizus and Aspergillus , Exophiala , and Fusarium species [ 85 , 86 , 87 , 88 , 89 ], where discrimination of the infecting species is needed to optimise treatment with antifungal drugs, and to prevent breakthrough R. arrhizus infections [ 70 , 90 ]. The detection of mucormycosis is not possible using the pan-fungal (1→3)-β- d -glucan (BDG) test, since the Mucorales lack this carbohydrate in their cell walls [ 91 ].…”
Section: Discussionmentioning
confidence: 99%
“…1 A limitation of the cranial MRI is the lack of fungal-specific findings and the difficulty in evaluating the results, especially in children with granulocytopenia or immunosuppression. 1,3 The most frequently reported findings in children with CNS IMD are fungal abscesses and inflammation of the parenchyma (cerebritis). 6 Data from a pediatric case series suggested that affection of cerebral blood vessels (infections and/or perivascular micro-bleeding) might indicate poor outcomes.…”
Section: Diagnostic Pillars For Pediatric Cns Imdmentioning
confidence: 99%
“…6 Data from a pediatric case series suggested that affection of cerebral blood vessels (infections and/or perivascular micro-bleeding) might indicate poor outcomes. 1,6…”
Section: Diagnostic Pillars For Pediatric Cns Imdmentioning
confidence: 99%
See 1 more Smart Citation
“…Children with haematological malignancies and those undergoing haematopoietic stem cell transplantation (HSCT) are at risk of developing invasive fungal infections [ 1 ]. Despite improvements in diagnostic tools and therapeutic options, the morbidity and mortality related with invasive mycoses in children remains high [ 1 , 2 , 3 , 4 , 5 , 6 ].…”
mentioning
confidence: 99%